Response of plant growth regulators and organic manure on growth attributes of cucumber (Cucumis sativus L.) hybrid under greenhouse conditions - Vedika, S; Amit, S; Yashpal, S B; Anand, S R; Megha, A; Shweta; Ruksana; Priya, T; Mamta, P (Plant Science Today, 2026)
Cucumber cultivation in the Sirmour region faces significant challenges, resulting in lower yields than in other regions. Optimizing fertiliser management is crucial to improving cucumber growth. A research trial was carried out at the Dr Khem Singh Gill Akal College of Agriculture, Eternal University, Sirmour, Himachal Pradesh, to examine the impact of organic manure and plant growth regulators (PGRs) on cucumber growth. The study included 64 treatment combinations, including the 3 organic fertilizers: vermicompost (5 t ha-1), biochar (2.5 t ha-1) and farmyard manure (FYM) (25 t ha-1). Three PGRs, namely 2,3,5-Triiodobenzoic acid (TIBA) (10 ppm), kinetin (10 ppm), brassinosteroids (2.0 ppm) and four hybrids, namely Aviva, Adiva, Fadia and Aafreen. The results revealed that the Aviva hybrid combination with vermicompost and brassinosteroids recorded the highest values for days to 1st flowering (DF), days to 1st female flowering (DFFF), internodal length (IL), node of 1st female flower, horizontal leaf width (HLW), horizontal leaf length (HLL), vine length (VL) and number of leaves per vine (NLV). A synergistic use of Aviva hybrid, vermicompost and brassinosteroids can effectively stimulate cucumber growth. Therefore, the integration of vermicompost with a foliar spray of brassinosteroids for the Aviva hybrid is recommended to farmers in the Sirmour district to improve vegetative characters.